Development of ANS PONG as a Tool for Block Training and Smash in Table Tennis Games (Journal of Physical Education and Sports, 2019)
Technology in table tennis sports, one of which is the ordinary ball launching robot called Robot drill. Expensive prices are one of the few causes that can be used. The purpose of this study is to: Develop ANS PONG product design for block and smash exercises, ANS PONG Production which is effective and affordable. The research method used is research and development. The results showed the quality of the product, based on the first expert evaluation, (table tennis lecturer) obtained a score of 90 excellent categories. Second expert evaluation (coach) with a score of 89 excellent categories. Evaluation of electronics experts with a score of 90 excellent categories. Conclusion: ANS PONG can be used as a block and smash training tool, effective as a block and smash training tool. It is recommended that ANS PONG is socialized and used for all athletes at relatively affordable prices. The advantages of ANS PONG That is using the remote control as a speed controller, ball spin and two-way drive fall of the ball, ANS PONG can also be set to a low height because it uses a tripod stand, using an Arduino microcontroller that can be set as desired, can for spin ball training, sidespin and backspin, easy to carry on sliding and move. It is recommended that ANS PONG be socialized and used for all athletes at relatively affordable prices.